Peningkatan Kecerdasan Interpersonal Anak Usia Dini Melalui Bermain - Andri Hardiyana (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah UI BBC, 2020)
The purpose of this study was to determine the increase in Interpersonal intelligence of early childhood through playing using the game techniques